PERANCANGAN USER INTERFACE APLIKASI PEMBELAJARAN BAHASA SUNDA PADA SEKOLAH DASAR NEGERI KAMOJING CIKAMPEK MENGGUNAKAN METODE DESIGN THINKING - Arif Ramdhani; Yudhi Raymond Ramadhan; Yusuf Muhyidin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Since the implementation of the 2013 curriculum, local language subjects have been taught in elementary schools. Learning local languages is important to maintain and preserve the language. SDN Kamojing Cikampek is located in West Java and is one of the schools for learning local languages, namely Sundanese. Many students are motivated to learn Sundanese at school, but there are also many students who have difficulty learning Sundanese. Given the innovation in the world of education today involves a lot of technology to carry out the learning process. There are many ways to learn Sundanese, one of which is through learning media that utilizes technology such as smartphones. With the support of technological innovation that is increasingly advanced, the role of user interface is important for user problem solving needs. The purpose of this research is to find out how we can use design thinking to meet and understand user needs. With the existence of Sundanese language learning media can help students learn Sundanese easily.